Spatial distribution of cetacean strandings in the Falkland Islands to define monitoring opportunities - Auge, Amelie A.; Otley, Hellen; Rendell, Nick; F. Frans, Veronica (J. Cetacean Res. Manage., 2023)
The waters around the Falkland Islands are used by many species of cetaceans, including endangered and data deficient species, but little is known about their populations. The Falkland Islands cetacean stranding database was transformed in a geo-spatial database using the available descriptions of the locations as no GPS locations were recorded until 2015. It was then used to analyse the spatial distribution of strandings over a period spanning the 1880s to 2015. A total of 169 stranding events could be given a location and mapped. Twelve stranding hotspots were identified. This paper also reports on the first recorded stranding of false killer-whales (Pseudorca crassidens) and Antarctic minke whale (Balaenoptera bonaerensis) in the Falkland Islands, increasing the total species recorded to 26. Spatially-explicit cetacean stranding databases can provide important data to monitor cetaceans in the light of environmental changes from climate change or industrial development. In the case of the Falkland Islands (remote and sparsely inhabited), identification of hotspots could be used to design an aerial monitoring programme to increase chances of detecting stranding events, organise a rescue or necropsy team to gain samples. The results in this paper should enhance local capacity to conduct research (sample collection for pollutant analyses, genetic studies, etc.) and monitor impacts of human activities on cetacean populations, including from the historical baseline of average numbers and distribution of strandings provided.